CRESCIMENTO INICIAL DE CLONES DE EUCALIPTO SUBMETIDOS A DESRAMA ARTIFICIAL - VIEIRA, V. A. C.; CACAU, F. V. P.; GOUVÊA, A. F .G.; FALCÃO, K. S.; MOREIRA JUNIOR, U. C.; PEREIRA, P. R. (ANAIS DO ENIC, 2016)
-